A simple in situ synthesis of iron oxide magnetic nanoparticles embedded in thermosensitive polymer for DNA capture. Issue 18 (28th September 2020) - Hossain, Sadia; Rahman, Mahbubor; Nahar, Yeasmin; Rahman, Abdur; Sharafat, Mostafa Kaiyum; Hossain, Motahar; Ochiai, Bungo; Elaissari, Abdelhamid; Ahmad, Hasan
Abstract: Abstract : In this study, we report a simple one-pot synthesis of iron oxide nanoparticles (IONPs) modified with thermoresponsive polymers potentially applicable for nucleic acid capture. Ferrous (Fe 2+ ) and ferric (Fe 3+ ) ions were coprecipitated to a dispersion of previously prepared poly( N -isopropylacrylamide-co-2-aminoethyl methacrylate) P(NIPAAm- co -AEM) for in situ synthesis of magnetite (Fe3 O4 ) and concurrent surface modification of Fe3 O4 with the polymer to obtain magnetic nanocomposites. Fourier-transform infrared (FTIR) spectroscopy analysis reveals the surface modification of Fe3 O4 with P(NIPAAm- co -AEM) and P(NIPAAm) as functional and control polymers, respectively. Fe3 O4 @P(NIPAAm- co -AEM) and Fe3 O4 @P(NIPAAm) nanocomposites' surfaces contain 7.5 and 2.3 wt% of immobilized polymers, respectively. Vibrating sample magnetometry (VSM) result indicates a high saturation of magnetization value, 75 emu/g, for Fe3 O4 @P(NIPAAm- co -AEM) nanocomposites. The hydrodynamic diameter of Fe3 O4 @P(NIPAAm- co -AEM) in water changes depending on pH and temperature. A study for deoxyribonucleic acid (DNA) capture ability of Fe3 O4 @P(NIPAAm- co -AEM) nanocomposites shows a maximum 18.5 mg/g of DNA can be adsorbed on Fe3 O4 @P(NIPAAm- co -AEM).